The Influence of Marketing Statements Found in Women’s Cosmetic Products to Their Mindset in Determining the Definition of Beauty - Amelia Yuli Astuti; Febi Oktisyafyeni (Jurnal Ilmiah Langue and Parole, 2018)
This journal discusses about the influence of the marketing statements found in women’s cosmetic products to their mindset in determining the definition of beauty. The writer takes the data from the marketing statements that happened in the commercial advertisements of four most used and commonly shown in audio visual media, such as television, which are Pond’s, Citra, Shinzui, and Garnier. The Technique of collecting the data of this thesis is the observation technique which then continued by writing down the conversatios that includes the marketing statements of the commercial advertisements into a form of a transcription. The writer uses the speech-act theory by John Langshaw Austin to analyze the influence of the marketing statements which presented through the conversations in the commercial advertisements, the theory of signs by Charles William Morris to analyze the signs that showed up in the commercial advertisements, and the theory of meaning by Charles Kay Ogden and Ivor Amstrong Richards to analyze the meaning of the symbols of signs that showed up in both the conversations and the narration. The result of this study shows that in every part of those products commercial advertisements, the marketing statements always try to influence the women to believe that indeed having white/bright/light skin means beautiful.